2016
DOI: 10.1002/jaba.326
|View full text |Cite
|
Sign up to set email alerts
|

Using token reinforcement to increase walking for adults with intellectual disabilities

Abstract: The purpose of this study was to evaluate the effectiveness of token reinforcement, using an ABAB reversal design, for increasing distance walked for adults with mild to moderate intellectual disabilities at an adult day-training center. Five participants earned tokens for walking 50-m laps and exchanged tokens for back-up reinforcers that had been identified through preference assessments. Token reinforcement resulted in a substantial increase from baseline in laps walked for 4 participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 5 publications
3
27
0
Order By: Relevance
“…First, during the token reinforcer assessment, we demonstrated that tokens functioned as reinforcers for all participants. These results provide empirical support for the use of token schedules with these individuals and contributes to the body of evidence, more broadly, of the effectiveness of token reinforcement with clinical populations (e.g., Eluri et al, ; Krentz et al, ; Tarbox et al, ). Although tokens are often assumed to function as reinforcers, empirical demonstrations of the reinforcing effect of tokens is relatively uncommon in applied research and practice (Hackenberg, ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…First, during the token reinforcer assessment, we demonstrated that tokens functioned as reinforcers for all participants. These results provide empirical support for the use of token schedules with these individuals and contributes to the body of evidence, more broadly, of the effectiveness of token reinforcement with clinical populations (e.g., Eluri et al, ; Krentz et al, ; Tarbox et al, ). Although tokens are often assumed to function as reinforcers, empirical demonstrations of the reinforcing effect of tokens is relatively uncommon in applied research and practice (Hackenberg, ).…”
Section: Discussionsupporting
confidence: 61%
“…Third, the token exchange schedule specifies the cost of terminal reinforcers in terms of tokens. Krentz, Miltenberger, and Valbuena (), for example, used a token economy to increase walking for adults with intellectual disabilities. Experimenters delivered a token to the participant for each lap completed (i.e., token production schedule).…”
Section: Introductionmentioning
confidence: 99%
“…LaLonde et al () used goal setting and a low‐cost prize‐based incentive intervention to increase steps taken during the school day among individuals diagnosed with autism, whereas Krentz et al () used a token economy to increase walking in individuals with intellectual disabilities during a day program. The current study was the first to examine a token economy for increasing steps in the context of a residential group home setting, where the intervention was carried out anytime the participant was in the group home and there were staff available to deliver tokens.…”
Section: Resultsmentioning
confidence: 99%
“…LaLonde, MacNeill, Eversole, Ragotzy, and Poling () used goal setting and a low‐cost prize‐based incentive intervention to increase steps taken during the school day among individuals diagnosed with autism. Finally, Krentz, Miltenberger, and Valbuena () used a token economy to increase walking among individuals with intellectual disabilities during a day program, and reported that the cost of the back‐up reinforcers ranged from $0.59 to $1.74 per day across participants, suggesting a relatively low‐cost approach. To the best of our knowledge, no previous studies have evaluated the use of a token economy to increase physical activity with adults diagnosed with intellectual or developmental disabilities in a residential living environment where it could be tracked throughout the entire day, rather than over a prescribed period of time.…”
mentioning
confidence: 99%
“…In addition, behavior analytic researchers have demonstrated how demand curve analyses can be successfully utilized as a conceptual and analytical paradigm for developing and evaluating public policy (e.g., Grant, 2007;Hursh & Roma, 2013). Finally, researchers using feedback and incentive-based strategies have already demonstrated behavior change across several of the five horsemen such as climate change (Foxx & Hake, 1977;Foxx & Schaeffer, 1981;Frazer & Leslie, 2014), and prevention of chronic disease and obesity (e.g., Krentz, Miltenberger, & Valbuena, 2016;Kurti & Dallery, 2013;Wengreen, Madden, Aguilar, Smits, & Jones, 2013). In addition, Biglan (2015) has illuminated how behavioral principles can aid in prevention and influence policy in many areas of society relevant to the horsemen.…”
mentioning
confidence: 99%